the transnationalization of the state in the process of an emerging eu migration control policy - Buckel, Sonja; Wissel, Jens (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
As a regional response to transnationalization the European integration has led to supranational institutions whose functions and competences had been core elements of nation statestill then. The development since 1999 has in particular brought about European politics of migration control which challenge classical approaches of (nation-) state theory. This is because these developments imply the emergence of a territory overlapping national boundaries, as they involve transnational population control and shifts in the state’s monopoly on the use of violence and citizenship legislation. Against this background, the aim of this article is to empirically analyse the new ensemble of institutions that is emerging with in this process. On the basis of the premise that the concreteform of the political is always the result of social struggles, we assume that the unity of the national territorial state is disintegrating in the processes described above. In fact, the state’s apparatuses re-groupwith European ones and form a reterritorialised and increasingly differentiated control apparatus which governs people alongside the constitution of zones of stratifi ed legal titles.
Keywords: Transnationalization; Migration; EU migration control policy..